2009
DOI: 10.1002/anie.200905088
|View full text |Cite
|
Sign up to set email alerts
|

Photo–Thermal Haptotropism in Cyclopentadienylcobalt Complexes of Linear Phenylenes: Intercyclobutadiene Metal Migration

Abstract: An attractive strategy for achieving solar-thermal energy conversion is to harvest sunlight in the form of activated chemical bonds through photoisomerization of a suitable molecule that can release, on demand, such stored and transportable energy by thermal reversal to its original form.[1] When such reversible isomerizations entail significant topological alterations, they provide blueprints for eliciting further functions, for example in switches, machines, datastorage, sensors, and other devices. [1,2] Bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 47 publications
2
25
0
Order By: Relevance
“…This observation has motivated anumber of gas‐phase studies on metal ion ligation to extended π‐systems 24. The incorporation of transition metal centers onto the surface of PAH systems can moderate their reactivity,25 as well as the photophysical26 and electronic19 properties of the hydrocarbon moiety. Transition metal functionalized PAHs also represent important models27 for the coordination of metals to graphene and other extended carbon surfaces 28…”
Section: Introductionmentioning
confidence: 99%
“…This observation has motivated anumber of gas‐phase studies on metal ion ligation to extended π‐systems 24. The incorporation of transition metal centers onto the surface of PAH systems can moderate their reactivity,25 as well as the photophysical26 and electronic19 properties of the hydrocarbon moiety. Transition metal functionalized PAHs also represent important models27 for the coordination of metals to graphene and other extended carbon surfaces 28…”
Section: Introductionmentioning
confidence: 99%
“…For the first time, in 1983, Albright et al7 Proposed a general qualitative rationalization of the haptotropic migration based on orbital interactions and electron counts using the semiempirical extended Hückel theory method. Recently, the density functional theory (DFT) and the correlated ab initio studies have confirmed these earlier qualitative results 8–16…”
Section: Introductionmentioning
confidence: 70%
“…A more inclusive term is haptotropic rearrangement [ 3 ] wherein a metal atom changes its hapticity along the reaction path. Haptotropic rearrangements in ML 3 and MCp complexes are numerous [ 4 9 ] and have found use in synthetic strategies [ 10 ], switching devices [ 11 13 ] and energy storage [ 14 15 ]. Much less is known about the polyene–ML 2 analogs.…”
Section: Introductionmentioning
confidence: 99%